PERAN NABI DALAM PROSES PEWAHYUAN ; Studi Kitab al-Nabaâu al-Azim Karya Muhammad âAbdullah Darraz - Zarkasyi, Ahmad; Lestari, Lenni (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Dawah of IAIN Langsa, 2018)
âAlquran is like a diamond shining over all the surfaceâ. That is well-known quote from Muhammad Abdullah Darraz in illustrating Alquran. From that statement, it is able to be summarized that he had provided a new paradigm of Alquran through his work, Al-Nabaâu Al-âAzim, Nazratun Jadidah fi Alquran. This paper will focus on several views in his book including the meaning of Alquran, hadis al-qudsi, hadis al-nabawi, wahyu al-nash, wahyu al-maâna, taâlim bi al-IbtidaâI, and taâlim bi al-Iqrar or naskh Intihaâi. Furthermore, this paper will analyze the theory of hadis al-qudsi I hadis al-nabawi and the consequences of classifiying Alquran, Hadis al-Qudsi, and Hadis al-Nabawi, including the role of the prophet in revelation methode. Based on Darrazâs view, Alquran is not able to be defined. The definition of Alquran which has been commonly known is only the efforts of traditional muslim scholars to approach the essential charachters of Alquran. The clearest differences among Alquran, hadis al-qudsi, and hadis al-nabawi are possible to be seen from three aspects. Those are, the way of revelation imparting (wahyu al-nash and wahyu al-maâna), textual indication (nash syarâi), and revelation purpose (taâabbud bi tilawatih and tahaddi (challenging). The principal philosophy of differentiating among Alquran, hadis al-qudsi, hadis al-nabawi is abridging the human to perform the religious obligation. The role of prophet Muhammad in revelation process is simply passive.